Dipyrone (metamizole) markedly interferes with platelet inhibition by aspirin in patients with acute and chronic pain: A case-control study. Issue 5 (May 2017) - Schmitz, Andrea; Roßmann, Larissa; Kienbaum, Peter; Pavlaković, Goran; Werdehausen, Robert; Hohlfeld, Thomas
Abstract : BACKGROUND: Nonopioid analgesic drugs may interfere with platelet inhibition by aspirin. Recent in vitro and clinical studies in patients with cardiovascular disease have suggested that this pharmacodynamic interaction may also occur with dipyrone, a nonopioid analgesic popular in Europe, Asia and South America. OBJECTIVE: Dipyrone is used extensively in acute and chronic pain. This study was undertaken to providec linical data, so far missing, on its interactions in this group of patients. DESIGN: A case-control study. SETTING: Primary care in one European university hospital centre. PATIENTS: In total, 27 patients with stable cardiovascular, cerebrovascular or peripheral arterial disease and acute or chronic pain were identified and given dipyrone for at least 5 days in combination with low-dose aspirin. In total, 10 comparable patients on low-dose aspirin alone served as controls. MAIN OUTCOME MEASURES: Platelet-rich plasma was prepared to determine arachidonic acid-induced aggregation (aggregometry) and thromboxane formation (immunoassay). Platelet sensitivity to aspirin was examined in vitro . The presence of dipyrone (metabolites) in plasma was confirmed by HPLC. Additional in vitro measurements examined the aspirin/dipyrone interaction in healthy donors. RESULTS: Inhibition of aggregation was observed in only six of 27 patients receiving aspirin with dipyrone, with absence of complete inhibition by antiplatelet therapy showing in 78% of patients. In contrast, aggregation was completely inhibited in nine of 10 control patients ( P < 0.001). Platelet thromboxane synthesis was higher in patients receiving dipyrone + aspirin compared with controls (387 ± 89 vs. 7 ± 1 ng ml −1, P < 0.001). Aspirin added in vitro failed to inhibit aggregation and thromboxane synthesis in platelet-rich plasma from dipyrone-treated patients. In vitro measurements with blood from healthy individuals confirmed that dipyrone dramatically reduces inhibition of platelet thromboxane synthesis by aspirin. CONCLUSIONS: Dipyrone given for 5 days or longer blunts platelet inhibition by low-dose aspirin in the majority of recipients. TRIAL REGISTRATION: German Clinical Trials Register: DRKS ID DRKS00000204. Universal Trial Number (UTN): U1111-1113-3946.